2011
DOI: 10.4236/ica.2011.23026
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning Based on the Cooperation of Cerebellum and Basal Ganglia for a Self-Balancing Two-Wheeled Robot

Abstract: A novel motor learning method is present based on the cooperation of the cerebellum and basal ganglia for the behavior learning of agent. The motor learning method derives from the principle of CNS and operant learning mechanism and it depends on the interactions between the basal ganglia and cerebellum. The whole learning system is composed of evaluation mechanism, action selection mechanism, tropism mechanism. The learning signals come from not only the Inferior Olive but also the Substantia Nigra in the beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…According to Newton's laws of motion, an external force produces an angular acceleration x(t) of the single-wheel car. While the single wheel robot becomes stable, the force along the direction perpendicular to the ground can be estimated by the model inclination angle and the acceleration of the wheel movement [15,17,18].…”
Section: Analysis Of Robot Load-carrying Capabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…According to Newton's laws of motion, an external force produces an angular acceleration x(t) of the single-wheel car. While the single wheel robot becomes stable, the force along the direction perpendicular to the ground can be estimated by the model inclination angle and the acceleration of the wheel movement [15,17,18].…”
Section: Analysis Of Robot Load-carrying Capabilitymentioning
confidence: 99%
“…When t = 1, x(t) = x(1), and c = x(1) − u a , according to Equation (17), it can obtain the discrete form differential equation, as shown in Equation (18).…”
Section: The Establishment Of the Gm (11) Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments showed that the combination of these two control algorithms could achieve a good control effect. Because of its small capacity, feasible rotation and strong ability to adapt to terrain changes, this combined algorithm is widely used in many fields [8][9][10], such as traffic, survey, rescue and entertainment. However, this method is cost prohibitive and time consuming because of its fuzzy rules.…”
Section: Introductionmentioning
confidence: 99%